Anti-vascular endothelial growth factor agent reduces inflammation in macular edema with central retinal vein occlusion - Asako Mashima; Hidetaka Noma; Kanako Yasuda; Hiroshi Goto; Masahiko Shimura (BMC, 2019)
Abstract Background Correlations among the aqueous flare value (an indicator of inflammation), functional-morphologic parameters, and aqueous humor levels of growth factors/receptors and inflammatory factors/cytokines were investigated in patients with central retinal vein occlusion (CRVO) and macular edema who received intravitreal ranibizumab injection (IRI) and were followed for 6 months. Methods Aqueous humor levels of 11 cytokines or growth inflammatory/factors were measured in 20 CRVO patients with macular edema receiving IRI. Patients with recurrent macular edema were administered further IRI as needed. Aqueous humor levels of vascular endothelial growth factor (VEGF), soluble VEGF receptor (sVEGFR), and other cytokines/inflammatory factors were measured by the suspension array method. Aqueous flare values were measured with a laser flare meter and macular edema was examined by optical coherence tomography. Results Compared with before treatment (baseline), the aqueous flare value showed a significant decrease at both 1 month and 6 months after IRI therapy. There were significant correlations between the aqueous flare value and the aqueous levels of sVEGFR-1, placental growth factor, monocyte chemoattractant protein 1, soluble intercellular adhesion molecule-1, interleukin (IL)-6, and IL-8. In addition, a significant correlation was noted between the change of the aqueous flare value and improvement of central macular thickness at 6 months after IRI, as well as a significant correlation between the change of the aqueous flare value and improvement of best-corrected visual acuity at 6 months. Conclusions These findings suggest that IRI reduces inflammation and that the aqueous flare value is influenced by inflammatory factors/cytokines. In addition, the change of the aqueous flare value may be an indicator of the long-term prognosis in CRVO patients receiving IRI therapy for macular edema.